2015
DOI: 10.1055/s-0034-1392223
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rectal suction versus rectal tube insertion for reducing abdominal symptoms immediately after unsedated colonoscopy

Abstract: Background and study aims: Abdominal discomfort and bloating are common symptoms after colonoscopy. We aimed to compare the effects of direct rectal suction with insertion of a rectal tube on reducing abdominal symptoms after unsedated colonoscopy. Patients and methods: Consecutive patients undergoing colonoscopy were randomized to have direct rectal suction or placement of a rectal tube immediately after colonoscopy. Post-procedure abdominal pain and bloating were measured with a 0 – 100 visual analogue scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Adequate bowel preparation is the premise of successful colonoscopy, and inadequate bowel preparation has a detrimental effect on the procedure [ 1 3 ]. Although colonoscopy with sedation has been widely applied, some patients still choose unsedated colonoscopy [ 4 , 5 ]. Because of the characteristics of unsedated colonoscopy, clinicians and medical staff need to be mindful of laxative tolerability and pain during colonoscopy [ 6 ] as well as the outcomes of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate bowel preparation is the premise of successful colonoscopy, and inadequate bowel preparation has a detrimental effect on the procedure [ 1 3 ]. Although colonoscopy with sedation has been widely applied, some patients still choose unsedated colonoscopy [ 4 , 5 ]. Because of the characteristics of unsedated colonoscopy, clinicians and medical staff need to be mindful of laxative tolerability and pain during colonoscopy [ 6 ] as well as the outcomes of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 In another study, rectal aspiration applied right after colonoscopy was found to be more effective in decreasing abdominal symptoms compared to the application of rectal tubes after colonoscopy. 5 In another study where total colonic decompression through repeating cecal intubation after colonoscopy was applied, the method was found to decrease the distension complaints of patients in the early post colonoscopy period from 59% to 25%. However, in this study, no significant difference between the groups that did and did not receive decompression with regard to abdominal pain and distension could be found 24 to 48 hours after the procedure.…”
Section: Introductionmentioning
confidence: 96%
“…Abdominal pain, bloating, and discomfort are the most frequently problems experienced by patients undergoing colonoscopy. [1][2][3][4][5][6] These problems are thought to be caused by several factors such as the duration of the process, the technical difficulty level of the process, distension caused by air insufflation, and the expertise level of the endoscopist. 4,7 These problems are experienced by approximately a third of patients undergoing colonoscopy, and may last from a few hours to a few days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that anorectal sensory function is regulated by brain-gut interactions with a link to sensorimotor response of rectoanus during rectal distension [ 5 ]. It is yet unclear whether feeling of abdominal discomfort during rectal distension is physiologically influenced by direct rectal decompression, although we had shown that direct rectal suction helps relieve abdominal symptoms immediately after colonoscopy [ 6 ]. This study was designed to evaluate the effect of rectal decompression on abdominal symptoms following rectal air distension.…”
Section: Introductionmentioning
confidence: 99%